Sulfur and nitrogen removal of model fuel using activated carbon derived from oil palm shell - S. M. Anisuzzaman; Awang Bono; Duduku Krishnaiah; Collin G. Joseph (Universiti Malaysia Sabah, 2015)
This research was done to understand the suitability and effectiveness of oil palm shells (OPS) as low cost adsorbents via physically activation with carbon dioxide (CO2) as an adsorbent for desulphurization and denitrogenation of a model fuel under different concentration. Batch mode experiments were conducted to study the effects concentration of Benzothiophine, Quinoline and Indole. Activated carbon (AC) was prepared at three different activation temperatures (500°C, 600°C, and 700°C), which was characterized with Scanning Electron Microscopy (SEM), Fourier Transform Infrared Spectroscopy (mR), and a mercury intrusion porosimeter. After adsorption, the solution was analysed with a Gas Chromatography (GC). Equilibrium adsorption isotherms and kinetics were investigated. The experimental data were analysed by the Langmuir and Freundlich models of adsorption. The adsorption isotherm data were fitted well to Langmuir isotherm and the most adsorption capacity on the best suited AC for Benzothiophene, Quinoline, and Indole were 3.64 mg/g, 4.19 mg/g and 2.98 mg/g respectively. The rates of adsorption were 0.19409 h-1, 0.08411 h-1, and 0.02883 h-1 for the adsorption of Benzothiophene, Quinoline, and Indole respectively. The kinetic data obtained at different concentrations have been analysed using a pseudo-first-order, pseudo-second-order equation and intraparticle diffusion equation. The pseudo-firstorder model best described the sorption process and was employed in predicting the rate constant, equilibrium sorption capacity as well.